Comparative analysis of using transmission and receiving diversity methods in WiMAX technology - Loshakov, V.; Vadia, Z.; Hasan, A. (ХНУРЭ, 2009)
WiMAX o f 802.16e standard is a very promising wireless technology which can support transmission rate about 45Mbit/sec. By adding the fast mobility with the high bit rate WiMAX 802.16e is considered the future o f wireless networks. Because mobile WiMAX is not line o f sight technology it makes the multifading channels interference a very severe problem which challenges the WiMAX performance ability.
Keywords: радиотехника